KEMAMPUAN MENULIS PUISI BERDASARKAN MEDIA GAMBAR SISWA KELAS X SMK NEGERI 1 KUANTAN MUDIK - Tiara Dwi Permana; Nursal Hakim; Elmustian Rahman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research entitled the ability to write poetry based on the media image of the X grade students of SMK Negeri 1 Kuantan Mudik. The aim of this research is to find out the level of poetry writing ability based on media images of class X students of SMK Negeri 1 Kuantan Mudik. The research was designed by descriptive analysis method with a quantitative approach. The data is the result of the score of the ability to write poetry based on media images with the assessment rubric. The total sample are 86 students of grade X SMK Negeri 1 Kuantan Mudik with total sampling. The results of this research found the ability to write poetry based on the media image of grade X students of SMK Negeri 1 Kuantan Mudik with a low category are 9 students, a medium category are 55 students, and a high category are 22 students.Keywords: Ability,Writing, Poetry